Review on melanosis coli and anthraquinone-containing traditional Chinese herbs that cause melanosis coli - Ruiyuan Zhang; Cai Huang; Fan Wu; Ke Fang; Shujun Jiang; Yan Zhao; Guang Chen; Ruolan Dong (Frontiers Media S.A., 2023)
Backgrounds: The incidence of melanosis coli (MC) has gradually increased annually, attracting significant attention and efforts into this field. A potential risk for MC is the long-term use of anthraquinone laxatives in patients with constipation. Most traditional cathartic drugs are made from herbs containing anthraquinone compounds. This review aims to provide guidance for the application of traditional Chinese herbs containing anthraquinones for physicians and researchers.Materials and methods: We reviewed risk factors and pathogenesis of MC, and natural anthraquinones isolated from TCM herbs. We searched Pubmed and CNKI databases for literature related to MC with keywords such as"traditional Chinese medicine", "Chinese herbs", "anthraquinones", and "melanosis coli". The literature is current to January 2023 when the searches were last completed. After the literature retrieval, the TCM herbs containing anthraquinones (including component identification and anthraquinone content determination) applied in clinical were selected. According to the collected evidence, we provide a list of herbs containing anthraquinones that could cause MC.Results: We identified 20 herbs belonging to 7 families represented by Polygonaceae, Fabaceae, Rhamnaceae, and Rubiaceae, which may play a role in the pathogenesis of MC. Among these, the herbs most commonly used include Dahuang (Rhei Radix et Rhizome), Heshouwu (Radix Polygoni Multiflori), Huzhang (Rhizoma Polygoni Cuspidati), Juemingzi (Semen Cassiae), Luhui (Aloe) and Qiancao (Rubiae Radix et Rhizoma).Conclusion: Due to a lack of awareness of the chemical composition of TCM herbs, many patients with constipation and even some TCM physicians take cathartic herbal remedies containing abundant anthraquinones to relieve defecation disturbances, resulting in long-term dependence on these herbs, which is potentially associated with most cases of MC. When such treatments are prescribed, TCM physicians should avoid long-term use in large doses to reduce their harm on colonic health. Individuals who take healthcare products containing these herbs should also be under the supervision of a doctor.